2015
DOI: 10.1016/j.ijpddr.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Selection for anthelmintic resistant Teladorsagia circumcincta in pre-weaned lambs by treating their dams with long-acting moxidectin injection

Abstract: Administration of long-acting anthelmintics to pregnant ewes prior to lambing is a common practice in New Zealand. Today, most of these products contain macrocyclic lactone (ML) actives, which because of their lipophilic nature, are detectable in the milk of treated animals and in the plasma of their suckling offspring. This study was conducted to confirm the transfer of ML actives to lambs in the ewe's milk, and to assess whether this could result in selection for ML resistant nematodes in the lamb. Ninety, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…maintaining an adequate parasite refugia ( Barnes et al, 1995 ; Kaplan and Nielsen, 2010 ; Miller et al, 2012 ; Leathwick et al, 2012 ) and utilize selective treatment ( Gomez and Georgi, 1991 ; Nielsen et al, 2019 ), ensuring the current resistance status is identified and effective treatments are used, including combination products ( Leathwick et al, 2009 ; Dobson et al, 2011 ; Bartram et al, 2012 ; Leathwick, 2012 ; Miller et al, 2012 ), avoiding unnecessary use of drugs, e.g. long acting anthelmintics or prophylactic applications without evidence of necessity ( Sutherland et al, 1997 ; Leathwick et al, 2009 , Leathwick et al, 2015a , Leathwick et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…maintaining an adequate parasite refugia ( Barnes et al, 1995 ; Kaplan and Nielsen, 2010 ; Miller et al, 2012 ; Leathwick et al, 2012 ) and utilize selective treatment ( Gomez and Georgi, 1991 ; Nielsen et al, 2019 ), ensuring the current resistance status is identified and effective treatments are used, including combination products ( Leathwick et al, 2009 ; Dobson et al, 2011 ; Bartram et al, 2012 ; Leathwick, 2012 ; Miller et al, 2012 ), avoiding unnecessary use of drugs, e.g. long acting anthelmintics or prophylactic applications without evidence of necessity ( Sutherland et al, 1997 ; Leathwick et al, 2009 , Leathwick et al, 2015a , Leathwick et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of the model and incorporation of genetic mechanisms for anthelmintic resistance have been described in detail elsewhere ( Leathwick et al, 2019 ; Leathwick et al, 2015 ; Sauermann et al, 2019 ). Briefly, the model replicates the dynamics of the cyathostomin free-living and parasitic stages, the administration of anthelmintics and the subsequent build-up of resistant genotypes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such neither product used in this study is licensed for use in dairy ewes. [24] have shown that a macrocyclic lactone can be detected in the plasma of suckling lambs up to at least 20 days after it was administered to the dam and thus may select for resistant parasites within the lamb [25]. The transfer of anthelmintic via the milk to the lambs may also contribute to the reduction in FEC of lambs suckling dams receiving short-acting and long-acting macrocyclic-lactones [26].…”
Section: Other Implications Of Macrocyclic Lactone Usementioning
confidence: 99%
“…However, its efficacy has been diminished due to the occurrence of parasitic resistance in herds (5). Therefore, alternatives to chemical control have really been sought because of anthelmintic resistance and especially the potential for transfer of sub-effective doses to lambs in milk during lactation (6), among them, the ability of animals to generate an effective immune response. The ability for sheep to acquire and to express immunity against gastrointestinal nematodes is genetically controlled, and this varies substantially among different breeds (7).…”
Section: Introductionmentioning
confidence: 99%